Multimaterial Glass Fiber Probe for Deep Neural Stimulation and Detection. Issue 2 (20th November 2022) - Dai, Yi; Du, Minghui; Huang, Lu; Zheng, Jiajun; Wei, Lei; Qiu, Jianrong; Ren, Chaoran; Zhou, Shifeng
Abstract: The ability for simultaneous modulation and monitoring of neural activities in deep tissues and at the single‐cell level merits significant scientific and technological potential, yet is met with limited success using conventional probes. Here, a new type of tiny multimaterial glass fiber probe is proposed and successfully constructed with the combination of robust mechanical response, strong light‐delivering ability, and excellent electrochemical properties, based on high throughput and scalable co‐drawing strategy. Guided by the multimaterial integration principle, the configuration of the probes can be rationally tuned including their material combination, physical size, the number and spatial distribution of the electrode, and even the waveguide structure. The bending stiffness, optical loss, and electrical impedance can be controlled to be larger than 4900 N m −1 and as small as 0.01306 dB cm −1 and 19.63 MΩ µm 2 at 1 kHz, respectively. To prove the utility, it is demonstrated that the probes allow for simultaneous deep neural stimulation and detection for more than 2 weeks at a single cellular level. This work not only promotes the development of neuroscience and brain science through the ability to manipulate neural circuits in the deep brain but also provides new directions for expanding the scope of functional fibers. Abstract : A new type of multimaterial glass fiber probe with a combination of robust mechanical response, strong light‐delivering ability, and excellent electrochemical properties is constructed by a scalable thermal drawing strategy. The probes allow for long‐term simultaneous deep neural stimulation and detection at the single cellular level, which provides a promising potential for applications in neuroscience and brain science.